Radio Colouring of Parametrized Graphs - Rani, A. Vimala (Mathematics and Computer Science: Research Updates Vol. 2, 2025)
The radio colouring is a proper vertex colouring with constraints that any two vertices at distance two should receive different colour and colour differnce between adjacent vertices should be at lest one. Radio colouring concepts plays a major role in frequency assignment problems. The radio chromatic number of sunlet, bistar and pencil graph families has been investigated in detail in this chapter.